Pendampingan Pendidikan Inklusi Melalui Civic Engagement Menuju Moderasi Beragama di Madrasah Ibtidaiyah Tarbiyatusshibyan Bojonegoro - Fahru Rozi; Farida Isroani; Pramesti Wulandari; Mita Erliana; Fitriyatus Sholicha (Universitas Muhammadiyah Manado, 2026)
This community service project aims to examine the implementation of inclusive education and civic engagement toward religious moderation in madrasas. This research is expected to improve students' understanding of the importance of diversity, acceptance of differences, and the right to receive education without discrimination. This community service project is also expected to make a significant contribution to shaping a younger generation with a deep understanding of inclusive education and civic engagement to achieve sound religious moderation. The targeted outcomes of this research are to create an inclusive learning environment, strengthen tolerance and respect for differences, and improve student understanding. This study uses a qualitative method with a descriptive approach to examine the implementation of inclusive education through civic engagement toward religious moderation. The research subjects included teachers, students, and their parents. The research location was chosen because of its significant religious and cultural diversity.